Understanding and design of two-stage fermentation: A perspective of interspecies electron transfer. (October 2022) - Yang, Min; Watson, Jamison; Wang, Zixin; Si, Buchun; Jiang, Weizhong; Zhou, Bo; Zhang, Yuanhui
Abstract: Two-stage fermentation has been proposed as an enhancement of mainline single-stage anaerobic digestion due to its improved energy production and environmental performance. However, the two-stage system is still in its infancy, due to its inconsistent performance. Previous studies were conceived from an experimental point of view to investigate two-stage fermentation. Such studies did not reveal the mechanistic causes behind the superior or inconsistent performance of the two-stage process. This limits the understanding and further optimization of two-stage fermentation. Recent developments regarding interspecies electron transfer mechanism, which is believed to play a critical role in acetogenesis and methanogenesis, provide a new perspective for understanding and designing two-stage systems. To this end, the state-of-the-art of two-stage fermentation was critically analyzed from an energy recovery, organics conversion, and metabolic network perspective to elucidate the roles of the two stages. The second stage was found to be decisive (73%) for the energy recovery improvement of two-stage fermentation. Emphasis was placed on the alteration strategies of metabolic intermediates in the first stage were focused on since the distribution of intermediates highly affects interspecies electron transfer in the following stage. In addition, mechanisms and strategies of enhanced interspecies electron transfer in two-stage fermentation, including mediated interspecies electron transfer via hydrogen/formate diffusion and direct interspecies electron transfer were compared and discussed. Lastly, based on a normalized quantitative evaluation of 135 anaerobic fermentation processes and reactors as well as techno-economic analysis, prospects for further understanding the mechanisms, optimization strategies, design and application of two-stage fermentation were discussed. This study could provide new insights into biowaste valorization and biofuels production via two-stage fermentation. Highlights: Two-stage fermentation was critically analyzed based on interspecies electron transfer. Second stage was decisive for the energy recovery improvement of two-stage fermentation (73%). Mechanisms and strategies for enhancing interspecies electron transfer were compared and discussed. Quantitative comparison of anaerobic fermentation (135 processes and reactors) was conducted. Prospects for optimizing and designing of two-stage fermentation were discussed.